Effect of Qiao Meridian Massage Combined with Modern Rehabilitation Therapy on Children with Spastic Cerebral Palsy - YANG Qiuping; WANG Huijuan; CHEN Bichan; FANG Xuexia; YANG Yan; YE Yong; TANG Wei; ZHANG Hong (康复学报)
ObjectiveTo observe the effect of Qiao meridian massage combined with modern rehabilitation therapy on adductor muscle tone and gross motor function of children with spastic cerebral palsy (SCP).MethodsA total of 60 SCP children inpatients and outpatients in the pediatric rehabilitation specialist clinic of the acupuncture and massage rehabilitation department in the First Affiliated Hospital of Hunan University of Chinese Medicine from April 2020 to September 2021 were randomly divided into control group and experimental group, with 30 cases in each group. The control group received modern rehabilitation therapy mainly including active exercise, passive exercise, physical modality therapy and occupational therapy, etc. The active exercise was 30 min a time, and the other treatment was 20 min a time, once a day, five days a week, lasting for three months. The experimental group received Qiao meridian massage on the basis of the control group, and the Qiao meridian massage was 15 min a time, active exercise was 15 min a time, and other treatments were the same as that of the control group, once a day, five days a week, lasting for three months. Before and after treatment, the modified Ashworth scale (MAS) was used to assess the muscle tone of adductor muscles; goniometry was used to measure the range of motion (ROM) of adductor muscles; the gross motor function measure scale-88 (GMFM-88) dimension D and E were used to assess the motor functions; and the clinical efficacy of both groups was evaluated.ResultsCompared with that before treatment, MAS score of both groups decreased significantly after treatment, while ROM of adductor muscles, GMFM-88 D and E scores increased significantly after treatment, and the differences were statistically significant (P<0.05). Compared with the control group, MAS score of the experimental group was significantly lower after treatment, the ROM of adductor muscles was significantly larger, and GMFM-88 D and E scores were significantly higher (P<0.05). The total effective rate of the experimental group was 90.00% (27/30), and the total effective rate of the control group was 76.67% (23/30), with no statistically significant difference between the two groups (P>0.05).ConclusionQiao meridian massage combined with modern rehabilitation therapy can effectively improve spasticity of adductor muscles of children with SCP, reduce adductor muscle tone, improve ROM of hip joint and gross motor functions such as standing, walking, running and jumping, etc., which is recommended for clinical application.